Social And Economic Processes That Took Place In The Agricultural System Of Uzbekistan In The First Half Of The 20th Century - Akmamatov Otabek Yodgorovich (Genius Journals, 2023)
This article talks about the social and economic processes that took place in the agricultural system of Uzbekistan in the first half of the 20th century. Based on historical data, the author studied and analyzed specific aspects of the social and economic processes that took place in the agricultural system of Uzbekistan in the first half of the 20th century based on available scientific literature
Keywords: Agriculture; collectivization; Soviet government